Tunable electronic structure of monolayer semiconductor g-C2N by adsorbing transition metals: A first-principles study. (November 2016) - Zheng, Z.D.; Wang, X.C.; Mi, W.B.
Abstract: The electronic structure of transition metal (TM) adsorbed two-dimensional g-C2 N is investigated by first-principles calculations. Most of TM-adsorbed g-C2 N show metallic properties, but Ni and Zn adsorptions show a band gap of 0.6 and 1.6 eV. The maximum spin splitting of TM-adsorbed g-C2 N from Sc to Zn is 110, 186, 117, 100, 0, 515, 147, 64, 95 and 0 meV, respectively. The magnetic moments of adsorbed structure from Sc to Co are in the range from 0.15 to 2.11 μB, while in Ni, Cu and Zn adsorbed cases no magnetic moments appear. In Fe-adsorbed g-C2 N, the adsorption structure at site of Fe 12 generates a 90 meV band gap, where the adsorption sites at CC and CN rings are marked as Fe 1 and Fe 2 . The maximum spin splitting is 515, 412 and 750 meV as Fe atomic concentration is 5.56%, 11.11% and 16.67%. Our results can bring more significant basis on the design of spintronic and valleytronic devices. Graphical abstract: